Embryonic and neonatal waves generate distinct populations of hepatic ILC1s - Sparano, Colin; Solís-Sayago, Darío; Vijaykumar, Anjali; Rickenbach, Chiara; Vermeer, Marijne; Ingelfinger, Florian; Litscher, Gioana; Fonseca, André; Mussak, Caroline; Mayoux, Maud; Friedrich, Christin; Nombela-Arrieta, César; et al. (Science immunology, 2022)
Group 1 innate lymphoid cells (ILCs) comprising circulating natural killer (cNK) cells and tissue-resident ILC1s are critical for host defense against pathogens and tumors. Despite a growing understanding of their role in homeostasis and disease, the ontogeny of group 1 ILCs remains largely unknown. Here, we used fate mapping and single-cell transcriptomics to comprehensively investigate the origin and turnover of murine group 1 ILCs. Whereas cNK cells are continuously replaced throughout life, we uncovered tissue-dependent development and turnover of ILC1s. A first wave of ILC1s emerges during embryogenesis in the liver and transiently colonizes fetal tissues. After birth, a second wave quickly replaces ILC1s in most tissues apart from the liver, where they layer with embryonic ILC1s, persist until adulthood, and undergo a specific developmental program. Whereas embryonically derived ILC1s give rise to a cytotoxic subset, the neonatal wave establishes the full spectrum of ILC1s. Our findings uncover key ontogenic features of murine group 1 ILCs and their association with cellular identities and functions.
CRIS-Team Scopus Importer:2023-03-23